Carrying Capacity for Extensive Fishing in Bunter Lake Siak Hulu Sub-District Kampar District Riau Province Based on Chlorophyll-a - Zaini Hafiz; Asmika Harnalin Simarmata; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTCarrying capacity is defined as the ability of aquatic enviromment to support the life organism in that area. A study aimed to asses the aquatic carrying capacity based on choloropyll-a for extensive fishing was conducted in the Bunter Lake. Carrying capacity was determined based on primary productivity using chlorophyll-a. The research  was conducted July-August 2019. There were 3 stations namely station 1 (inlet area), station 2 (in the middle of the lake) and station 3 (in the end of the lake). In each stations, there were 2 sampling sites, in the surface and 2 Secchi depth. Sampling was done 4 time, once a week. Water quality parameter measured chlorophyll-a, nitrate, phosphat, dissolved oxygen, water transparency, temperature and pH. Result shown that chlorophyll-a 10.49-10.89 µg/L, nitrate 0.043-0.080 mg/L, phosphate 0.022-0.37 mg/L, dissolved oxygen 4.32-6.59 mg/L, water transparency 77.7-85.2 cm, temperature 29.5-30.5 ºC and pH 5. The concentration of chlorophyll-a indicate that carrying capacity of the Bunter Lake for extensive fishing was 0.73 tons/year.Key Word : chlorophyll-a, carrying capacity, water quality, bunter lake, primary productivity